Light-triggered OVA release based on CuS@poly(lactide-co-glycolide acid) nanoparticles for synergistic photothermal-immunotherapy of tumor. (August 2020) - Chen, Zhenzhen; Zhang, Qian; Zeng, Lingjun; Zhang, Jialiang; Liu, Zhihong; Zhang, Minxin; Zhang, Xueting; Xu, Hang; Song, Hongtao; Tao, Chun
Graphical abstract: Abstract: The immunotherapy played a vital role in the treatment of metastatic tumor. To further enhance the effect of the immunotherapy, the combination of photothermal effect can not only eradicate the tumor cells by hyperthermia, but also improved the antigen release in vivo to achieve enhanced immune responses. In this study, a core-shell structured nanocomplex was developed by loading of ovalbumin (OVA) and copper sulfide nanoparticles (CuS-NPs) into the poly(lactide-co-glycolide acid) nanoparticles (PLGA-NPs). The CuS-NPs exhibited favorable photothermal effect, which significantly kill the 4T1 tumor cells in vitro . The photothermal effect of the CuS-NPs accelerated the OVA release, which led to higher levels of IL-6, IL-12 and TNF-α, and activation of CD8 + T cells. Both of the OVA-PLGA-NPs and CuS-NPs with NIR light irradiation contributed inhibited primary tumor while the growth of the distant tumors was not hindered. The irradiated CuS@OVA-PLGA-NPs exhibited a minimal primary tumor because of the combined effect of photothermal therapy and immunotherapy. Moreover, the irradiated CuS@OVA-PLGA-NPs showed the most extensive distribution of CD8 + T cells in the primary and distant tumor, which blocked the rise of the distant tumor. In conclusion, the CuS@OVA-PLGA-NPs presented as a promising strategy for metastatic tumor therapy.